(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The study aimed to assess knowledge, attitudes and practices on domestic water use of people in Thanh Ninh commune, Phu Binh district, Thai Nguyen province in 2024. Materials and methods: The study cross-sectionally described over 400 people, using a set of survey questions to collect data, and analyzed using SPSS 26.0 software. Results: 78.8% of people have poor knowledge about domestic water. Standards for clean water such as colorless, odorless, tasteless, clear (81.3%) and not affecting human health (79.8%) account for a high proportion. However, understanding of chemical factors in the standards (19.3%) and biological factors in the standards (11.5%) is still limited. Regarding attitudes, over 90% of people have a positive attitude, showing awareness of using water, treating water and checking water quality properly. Regarding practice, 59% of people do not do it correctly, especially the amount of water they drink daily is not enough compared to the standards (65.2%) and the time to drink water is when thirsty (66.8%) is still high. However, people have treated water by boiling (82.5%) and water filters (97.5%) account for a high proportion. Conclusions: Most people have good awareness, but their knowledge and practice are still poor. There should be health education communication programs to guide people on how to use water properly, safely and appropriately